2022
DOI: 10.1038/s41419-022-05083-2
|View full text |Cite
|
Sign up to set email alerts
|

SARM1 deletion in parvalbumin neurons is associated with autism-like behaviors in mice

Abstract: Autism spectrum disorder (ASD), a group of neurodevelopmental disorder diseases, is characterized by social deficits, communication difficulties, and repetitive behaviors. Sterile alpha and TIR motif-containing 1 protein (SARM1) is known as an autism-associated protein and is enriched in brain tissue. Moreover, SARM1 knockdown mice exhibit autism-like behaviors. However, its specific mechanism in ASD pathogenesis remains unclear. Here we generated parvalbumin-positive interneurons (PVI)-specific conditional SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Consistent with previous study [ 45 ], the present study found that SARM1 was mainly expressed in brain neurons, and the expression of neuronal SARM1 was decreased in 9-month-old APP/PS1 model mice ( Fig. 1 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous study [ 45 ], the present study found that SARM1 was mainly expressed in brain neurons, and the expression of neuronal SARM1 was decreased in 9-month-old APP/PS1 model mice ( Fig. 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…Some previous studies have shown that in SARM1 knockdown mice, dendritic arbors of neurons were less complex, and suggested that SARM1 is required for proper initiation and elongation of dendrites, axonal outgrowth, and neuronal polarization [ 47 ]. Our previous study has shown that parvalbumin-positive interneurons (PVI)-specific conditional SARM1 deletion (SARM1 PV -CKO) mice exhibited autism-like behaviors and a reduction in the number of PVIs due to apoptosis, suggesting that SARM1 deficiency in PVIs may contribute to the pathogenesis of autism spectrum disorder [ 45 ]. However, our recent studies suggested that there was no significant difference in the neuronal number and distribution in the spinal cords between SARM1 f/f and SARM1 Nestin -CKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the emergence of PV neurons in the visual cortex of rodents coincides with the onset of the critical period for visual plasticity (del Río et al, 1994;Sugiyama et al, 2008;Takesian and Hensch, 2013;Cisneros-Franco et al, 2020), and manipulations of PV expression affect plasticity and the timing of critical periods for sensory and cognitive systems (Murray et al, 2015;Wöhr et al, 2015;Hou et al, 2017;Xia et al, 2017;Cisneros-Franco and de Villers-Sidani, 2019;Deng et al, 2019;Miranda et al, 2022). Furthermore, manipulations of PV neuron activity affects neural dynamics across various brain systems (e.g., Spiro et al, 1999;Cardin et al, 2009;Sohal et al, 2009;Pyka et al, 2011;Albéri et al, 2013;Liu et al, 2013;Hu et al, 2014;Xue et al, 2014;Wöhr et al, 2015;Xia et al, 2017;Carceller et al, 2020), and PV neuron dysfunction can lead to cognitive and behavioral dysfunctions (Cardin et al, 2009;Sohal et al, 2009;Hu et al, 2014;Wöhr et al, 2015;Enwright et al, 2016;Favuzzi et al, 2017;Xiang et al, 2022). Therefore, it is important to reveal the factors that influence PV expression.…”
Section: Introductionmentioning
confidence: 99%
“…Both SARM1 and ASK1 regulate Toll-like receptor (TLR) signaling, a key signaling arm of innate immunity ( Liu et al, 2014 ; Matsuzawa, 2017 ), and act via JNK to promote “forgetting” in C. elegans olfactory neurons ( Inoue et al, 2013 ). Loss of SARM1 also leads to impairments in synaptic plasticity ( Lin et al, 2014 ) and loss of parvalbumin neurons associated with autism-like behaviors ( Xiang et al, 2022 ).…”
Section: Sarm1-regulated Signaling Mediates Diverse Functions Includi...mentioning
confidence: 99%